Characterization of silicon tunnel field effect transistor based on charge plasma - Firas Natheer Abdul-kadir; Faris Hassan Taha (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
The aim of the proposed paper is an analytical model and realization of the characteristics for tunnel field-effect transistor (TFET) based on charge plasma (CP). One of the most applications of the TFET device which operates based on CP technique is the biosensor. CP-TFET is to be used as an effective device to detect the uncharged molecules of the bio-sample solution. Charge plasma is one of some techniques that recently invited to induce charge carriers inside the devices. In this proposed paper we use a high work function in the source (ϕ=5.93 eV) to induce hole charges and we use a lower work function in drain (ϕ=3.90 eV) to induce electron charges. Many electrical characterizations in this paper are considered to study the performance of this device like a current drain (ID) versus voltage gate (Vgs), ION/IOFF ratio, threshold voltage (VT) transconductance (gm), and sub-threshold swing (SS). The signification of this paper comes into view enhancement the performance of the device. Results show that high dielectric (K=12), oxide thickness (Tox=1 nm), channel length (Lch=42 nm), and higher work function for the gate (ϕ=4.5 eV) tend to best charge plasma silicon tunnel field-effect transistor characterization.